2013
DOI: 10.1523/jneurosci.5810-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Imprinting Effects of the X Chromosome on Brain Morphology

Abstract: There is increasing evidence that genomic imprinting, a process by which certain genes are expressed in a parent-of-origin specific manner, can influence neurogenetic and psychiatric manifestations. While some data suggest possible imprinting effects of the X-chromosome on physical and cognitive characteristics in human, there is no compelling evidence that X-linked imprinting affects brain morphology. To address this issue, we investigated regional cortical volume, thickness and surface area in 27 healthy con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 50 publications
5
30
0
1
Order By: Relevance
“…Thus, in this sample, we are able to examine the effects of absence of one complete X chromosome on amygdala structure before the administration of exogenous estrogen. The sample used in this study overlaps with previously published work [Hong et al, ; Lepage et al, ]. The local Institutional Review Board of the Stanford University School of Medicine approved this study and informed written consent was obtained from a legal guardian for all participants.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, in this sample, we are able to examine the effects of absence of one complete X chromosome on amygdala structure before the administration of exogenous estrogen. The sample used in this study overlaps with previously published work [Hong et al, ; Lepage et al, ]. The local Institutional Review Board of the Stanford University School of Medicine approved this study and informed written consent was obtained from a legal guardian for all participants.…”
Section: Methodsmentioning
confidence: 99%
“…Most of the studies analyzing parent-of-origin effects in TS, report a predominance of the maternal X, largely due to the non-viability of the karyotype 45,Y and a slight preferential loss of paternal sex chromosomes (66, 67,68,69,70,71). Several studies analyzed whether X-linked imprinting effects might be associated with distinct phenotypical features, with conflicting results (72,73,74). Lack of statistical power to detect subtle differences explains part of the observed heterogeneity (Table 4).…”
Section: Postnatal Diagnosismentioning
confidence: 99%
“…Male embryos inherit only the maternal X, while female embryos inherit both a maternal and paternal X [132]. Differences in the phenotype of XO girls who inherit a paternal (X p ) vs. a maternal (X m ) Xchromosome, suggest that X-chromosome imprinting does impact development, particularly in the brain [132,134]. Intriguingly, one study found a trend towards increased brain volume in X m O girls, compared to X p O girls [134], suggesting potential roles of X imprinted genes on regulating growth.…”
Section: Sex Differences In Epigeneticsmentioning
confidence: 99%